2014
DOI: 10.1080/01639269.2014.912104
|View full text |Cite
|
Sign up to set email alerts
|

Librarians’ Views on Critical Theories and Critical Practices

Abstract: This study was conducted to investigate levels of familiarity that librarians have with critical theory, to determine the extent to which it informs professional practices, and to examine how the social justice issues related to critical theory inform the practices of librarians who are unfamiliar with it. A survey found that librarians were versed not only in the critical theory of the Frankfurt School, but also in poststructuralism, feminism, queer theory, critical race theory, and postcolonialism. Many libr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…23 A recent survey found that a number of librarians have familiarity with one of a number of critical theories, from postcolonialism to queer theory, and moreover, that many librarians are concerned with social justice issues as they relate to libraries. 24 At the same time, examples of how critical IL is and can be practiced, as well as how different factors facilitate or inhibit critical IL work, are lacking from the existing literature. The gap between an increasing interest in critical IL and its application to one's work is what this research intends to address.…”
Section: Literature Reviewmentioning
confidence: 99%
“…23 A recent survey found that a number of librarians have familiarity with one of a number of critical theories, from postcolonialism to queer theory, and moreover, that many librarians are concerned with social justice issues as they relate to libraries. 24 At the same time, examples of how critical IL is and can be practiced, as well as how different factors facilitate or inhibit critical IL work, are lacking from the existing literature. The gap between an increasing interest in critical IL and its application to one's work is what this research intends to address.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To prepare LIS students and graduates to confront oppression, to understand "how power and privilege shape LIS institutions and professional practice" (Cooke et al 2016, 107), to embrace social justice as an LIS value (Pawley 2006;Schroeder and Hollister 2014;Cooke et al 2016), and to understand the ethical implications of their decisions and practices requires that faculty intentionally help students develop the theoretical, practical, and ethical foundations they will need to engage with marginalized and silenced communities in ways that prioritize community needs and uphold the values of the profession. It requires faculty to prepare students to employ critical theories and methods as they incorporate the perspectives and values of marginalized and silenced communities, examine how libraries participate in systems of oppression, explore ways for librarians to dismantle these systems, and guide their efforts to work with "patrons and communities to co-investigate the political, social, and economic dimensions of information, including its creation, access, and use" (Tewell 2016, par.…”
Section: Build Students' Theoretical Practical and Ethical Foundationsmentioning
confidence: 99%
“…They should prepare their students so that when they go out into their communities, a diverse collection is a naturally occurring phenomenon. Schroeder and Hollister (2014) worked with various types of librarians to understand their level of fluency with the concepts of critical theories, including CRT. They found that whether or not librarians understood what it was, they still identified advocating for social justice in their information communities as one of their main goals.…”
Section: Implications For Wndbmentioning
confidence: 99%